Post-Traumatic Segmental Tibial Defects Management: A Systematic Review of the Literature - Giovanni Marrara; Biagio Zampogna; Viktor Dietrich Schick; Leone Larizza; Paolo Rizzo; Ilaria Sanzarello; Matteo Nanni; Danilo Leonetti (Applied Sciences)
Introduction: Segmental tibial defects pose significant challenges in orthopedic surgery due to their complexity and high complication rates. This systematic review aimed to evaluate both the effectiveness and outcomes of distraction osteogenesis (D.O.) and the Masquelet technique in treating post-traumatic segmental tibial defects. Materials and Methods: A literature search was performed on PubMed, Scopus, and Cochrane. Relevant retrospective and prospective observational studies with a minimum of 12 months follow-up were included. The primary outcome was bone union rate; the secondary outcomes were the type and rate of complications and the clinical and radiological outcomes. Results: Twenty-seven studies met the inclusion criteria, 18 studies reported data on D.O. and 9 on the Masquelet technique. D.O. demonstrated an overall union rate of 79.4% across 422 patients, and the Masquelet technique demonstrated an overall bone union rate of 85% across 113 patients. For D.O., on average, there was one complication per patient, and with the Masquelet technique, there were 0.5 complications per patient. Conclusions: D.O. and the Masquelet technique are the main treatment options for post-traumatic segmental tibial defects. Although union rates are similar, the Masquelet technique showed fewer complications. Treatment choice should consider patient-specific factors and more comparative studies are needed.